Transformation of Human Resource Management in the Era of Digitalization of Indonesian Public Services - Solehudin Solehudin; Restu Jahira Dhawi Mughni (Publikasi Indonesia, 2025)
The digitalization of public services in Indonesia is a national strategic agenda in order to improve the effectiveness, transparency, and quality of services to the community. This change requires the transformation of Human Resource Management (HRM) so that the apparatus is able to adapt to technological developments, digital work systems, and increasingly complex performance demands. However, the readiness of human resources in facing digital transformation is still a major challenge in various public agencies. This research aims to analyze the role and transformation strategy of Human Resource Management in supporting the digitalization of public services in Indonesia, as well as identify the challenges and opportunities that arise in the transformation process. This study uses a qualitative method with a literature study approach. Data was obtained from various secondary sources such as scientific journals, books, government reports, and regulations related to the digitization of public services and HRM in Indonesia. The data is analyzed descriptive-analytically to gain a comprehensive understanding. The results of the study show that the transformation of HRM in the era of digitalization of public services includes strengthening the digital competence of apparatus, changing the work culture towards more adaptive and collaborative, and implementing a technology-based performance management system. In addition, leadership support, consistent policies, and ongoing training are key factors in the success of HRM transformation in digital public services.